Effects of Al2O3 on the leaching of fluorine in mold fluxes - GAO Jin-xing; WEN Guang-hua; TANG Ping; CHEN Li-yuan; YANG Chang-lin (工程科学学报)
In order to eliminate the hazard effects of the leaching of fluorine in mold fluxes,this paper introduces a mold flux with high Al2O3 content. The effects of Al2O3 content on the concentration of F- ions and the pH value of leaching water were investigated,and the dependence of Al2O3 on the structure of mold fluxes was analyzed by X-ray photoelectron spectroscopy(XPS). When the mass fraction of Al2O3 is 4%,the concentration of F- ions in leaching water is about 22.8 to 35.4 mg·L-1,and the pH range is between 4.0 and 9.5. The F- concentration and the pH range initially reduces and then slightly rises again as the Al2O3 content increases from 4% to 34%. The XPS spectra show that the Al-F bond forms in the mold flux when the Al2O3 content increases. This can restrain the dissolution of fluorine in water. Controlling the content of Al2O3 between 16% and 34%,the F- concentration in leaching water is about 4.0 to 10.0 mg·L-1,and the pH range is between 6.5 and 7.5. This is helpful to reduce the hazard effects of the leaching of fluorine in mold fluxes.